Bone regeneration of a polymeric sponge technique—Alloplastic bone substitute materials compared with a commercial synthetic bone material (MBCP+TM technology): A histomorphometric study in porcine skull. Issue 5 (6th January 2021) - Intapibool, Punyada; Monmaturapoj, Naruporn; Nampuksa, Katanchalee; Thongkorn, Kriangkrai; Khongkhunthian, Pathawee
Abstract: Background: Polymeric sponge technique is recommended for developing the desired porosity of Biphasic calcium phosphate (BCP) which may favor bone regeneration. Purpose: To investigate the healing of BCP with ratio of HA30/β‐TCP70 (HA30) and HA70/β‐TCP30 (HA70) polymeric sponge preparation, compare to commercial BCP (MBCP+TM). Materials and Methods: Materials were tested X‐ray diffraction (XRD) pattern and scanning electron microscope (SEM) analysis. In eight male pigs, six calvarial defects were created in each subject. The defects were the filled with 1 cc of autogenous bone, MBCP+TM (MBCP), HA30, HA70, and left empty (negative group). The new bone formations, residual material particles and bone‐to‐graft contacts were analyzed at 4, 8, 12 and 16 weeks. Results: Fabricated BCP showed well‐distributed porosity. At 16 weeks, new bone formations were 45.26% (autogenous), 33.52% (MBCP), 24.34% (HA30), 19.43% (HA70) and 3.37% (negative). Residual material particles were 1.88% (autogenous), 17.58% (MBCP), 26.74% (HA30) and 37.03% (HA70). These values were not significant differences (Bonferroni correction <0.005). Bone‐to‐graft contacts were 73.68% (MBCP), which was significantly higher than 41.68% (HA30) and 14.32% (HA70; Bonferroni correction <0.017). Conclusions: Polymeric sponge technique offers well‐distributed porosity. The new bone formation and residual material particles were comparable to MBCP+TM, but the bone‐to‐graft contact was lower than MBCP+TM.